Utilisation of genetic markers for the presymptomatic diagnosis of familial adenomatous polyposis (FAP) - Hayes, Vanessa M (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1995.